2011
DOI: 10.1103/physrevb.84.144523
|View full text |Cite
|
Sign up to set email alerts
|

Pair breaking versus symmetry breaking: Origin of the Raman modes in superconducting cuprates

Abstract: We performed Raman scattering experiments on superconductivity-induced features in Bi2Sr2(Ca1−xYx)Cu2O 8+δ (Bi-2212), YBa2Cu3O6+x (Y-123), and Tl2Ba2CuO 6+δ (Tl-2201) single crystals. The results in combination with earlier ones enable us to systematically analyze the spectral features in the doping range 0.07 ≤ p ≤ 0.24. In B2g (xy) symmetry we find universal spectra and the maximal gap energy ∆0 to scale with the superconducting transition temperature Tc. The B1g (x 2 − y 2 ) spectra in all three compounds s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 133 publications
11
33
1
Order By: Relevance
“…(13) 64,65 . The B 1g and B 2g superconducting gaps were detected experimentally 77,82,85,94,95 . The absorption coefficient corrected low-energy spectra are shown in Fig.…”
mentioning
confidence: 94%
“…(13) 64,65 . The B 1g and B 2g superconducting gaps were detected experimentally 77,82,85,94,95 . The absorption coefficient corrected low-energy spectra are shown in Fig.…”
mentioning
confidence: 94%
“…This may, in an intuitive way, explain why the B 1g Raman response from the anti-nodal part of the Brillouin zone but also other two-particle susceptibilities such as the NMR relaxation rate 4,82,84 get depressed or incoherent much earlier than the single-particle response 3 . We suggest that the suppression of the B 1g coherence peaks in the superconducting state 43,85,86 can also be traced back to fluctuations of incipient charge order. This, of course, implies that the fluctuations are also present in Y123 or Bi2212 with high T max c even if they do not manifest themselves in an AL-type response at p > 0.05.…”
Section: Phase Diagrammentioning
confidence: 99%
“…Wakimoto et al 55 found the incommensurate spin order also to disappear there. If one examines the B 1g gap maxima on the overdoped side of the phase diagram 28,33,86,[89][90][91] , it becomes clear that the intensity increases beyond p = 0.21, which can hardly be traced back to coherence. Actually, the increase is so fast that a divergence point may be anticipated.…”
Section: Phase Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…In particular special care has been devoted to extract the pure A 1g spectrum from well controlled subtractions of the Raman spectra. Importantly, the doping level was solely controlled by oxygen insertion to avoid cationic substitutions which can drastically change the electronic Raman spectra [46]. The large range of doping levels from p=0.06 to p=0.23 was successfully obtained from specific annealing treatments described in the experimental procedure.…”
Section: Introductionmentioning
confidence: 99%